2008
DOI: 10.1158/0008-5472.can-07-3249
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer Binding Protein δ Up-regulates Aromatase Promoters I.3/II in Breast Cancer Epithelial Cells

Abstract: Aromatase is the enzyme responsible for the last step of estrogen synthesis. The female hormone, estrogen, is known to stimulate breast cancer cell growth. Because the expression of aromatase in breast cancer tissues is driven by unique promoters I.3 and II, a more complete understanding of the regulatory mechanism of aromatase expression through promoters I.3/II in breast tumors should be valuable in developing targeted therapies, which selectively suppress estrogen production in breast tumor tissue. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Recently, through in vivo footprinting analysis, we identified an important regulatory site at which C/EBPδ binds and up-regulates breast cancer-specific aromatase promoters I.3/II in breast cancer epithelial cells (44). Our review of the literature on HDAC inhibitors revealed that adiponectin gene expression can be suppressed by the HDAC inhibitor valproic acid, which decreases C/EBPα levels and lessens binding of C/EBPα to the adiponectin promoter (45).…”
Section: Lbh589 Suppresses Aromatase Expression Through Promoters I3mentioning
confidence: 93%
“…Recently, through in vivo footprinting analysis, we identified an important regulatory site at which C/EBPδ binds and up-regulates breast cancer-specific aromatase promoters I.3/II in breast cancer epithelial cells (44). Our review of the literature on HDAC inhibitors revealed that adiponectin gene expression can be suppressed by the HDAC inhibitor valproic acid, which decreases C/EBPα levels and lessens binding of C/EBPα to the adiponectin promoter (45).…”
Section: Lbh589 Suppresses Aromatase Expression Through Promoters I3mentioning
confidence: 93%
“…The role of aromatase in promoting breast cancer is well defined; factors derived from malignant epithelial cells such as prostaglandin E 2 as well as trans-acting transcription factors such as Liver Receptor Homologue (LRH-1/NR5A2), cAMP response element binding protein (CREB), Activating Transcription Factor 2 (ATF2/CREB2) and CCAAT/enhancer binding protein δ (C/EBPδ) increase aromatase levels within the epithelial cells and surrounding adipose stromal fibroblasts [9-11]. Additionally in breast cancers, the tumour inhibits adipose stromal fibroblast differentiation while in normal breast tissues differentiation into mature adipocytes reduces aromatase expression [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of aromatase expression is complex, but one of its key regulators is cAMP. cAMP activates the cAMP-responsive element binding protein (CREB), which interacts with CRE sites in the aromatase promoter I.3/II, inducing its transcription [36,37]. cAMP treatment of MCF-7 cells caused an approximately twofold increase in aromatase mRNA levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The model systems used in this study, JEG-3 human placental cells used as a source of microsomal aromatase and the estrogen-receptorpositive MCF-7 human mammary cancer cell line, have been used extensively in aromatase research [30][31][32][33]37,38] and thus are appropriate in vitro models. Plasma concentrations of ROH reach 2-3 μM in humans [2,39].…”
Section: Discussionmentioning
confidence: 99%